Effectiveness of Tactical Games Model Based on Teaching by Invitation for Enhance Learning Motivation and Physical Activity in Primary School Students - Nur, Lutfi; Muslihin, Heri Yusuf; Stephani, Mesa Rahmi; Wibowo, Ricky; Mustaqim, Ridha; Sianturi, Risbon; Annamayra, Ajeng; Malik, Arief Abdul; Nilan, Fariha (JUMORA: Jurnal Moderasi Olahraga, 2024)
The aim of this research was to examine the effectiveness of the Tactical Games learning model combined with the Teaching by Invitation technique in boosting both learning motivation and physical activity among elementary school students. This quasi-experimental study included three groups: the first group utilized the Tactical Games model integrated with the Teaching by Invitation technique, the second group applied solely the Tactical Games learning model, and the third group, serving as the control, followed the conventional learning model. Participants were fifth-grade students from three different schools in Tasikmalaya, Indonesia. To measure outcomes, three research instruments were employed: the Electronic Rubric for Motivation in Physical Education (eRMoPE) to assess learning motivation, the Polar GPS RC3, and the Polar Heart Rate Sensor H3 to evaluate the category of students' physical activity. Findings indicated that while all three approaches effectively enhanced learning motivation and physical activity, the combination of the Tactical Games model with the Teaching by Invitation technique yielded superior improvements. This integrative method grants students the autonomy to select skills they wish to learn and master, aligning with their abilities and understanding of game tactics adapted to specific game situations and environments. This freedom fosters a more engaging and personalized learning experience, ultimately enhancing both motivation and physical activity levels among students. The study highlights the potential benefits of blending tactical learning strategies with motivational techniques, suggesting a valuable approach for educators aiming to improve physical education outcomes in elementary schools